The Role of Satisfaction Customers as Mediator of the Influence of E-Service Quality and Perceived Price on Customer Loyalty in Gojek Online Transportation Services - Kurniawan, Aris; Marlinah, Lili; Noverha, Yosie (Universitas Muhammadiyah Palu, 2024)
This research aims to determine the influence of E-Service quality and price perception on customer loyalty, with a focus on the importance of customer satisfaction. The research conducted will explain the relationship between Eservice quality and price perception with customer loyalty directly and indirectly, namely through customer satisfaction as a mediating variable usingquantitative methodology. The research population is users of online transportation services. The sampling technique used purposive sampling, with a total sample of 150 respondents. The data collection technique uses an online questionnaire that has been tested. In the process of responding to the hypothesis through Structural Equation Modeling (SEM) research carried out with the help of Smart PLS version 3 software. The results of the research explain that e-service quality and price perception have a positive and significant effect on customer satisfaction, e-service quality and price perception have an effect positively and significantly on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, indirectly e-service quality has no effect on customer loyalty through customer satisfaction. Meanwhile, indirectly, price perception has a positive and significant influence on customer loyalty through customer satisfaction.